E Evaluation of Ultima InfoSys Site Usability Using Usability Test & System Usability Scale Method - Clarita Putri; Rudi Sutomo (Universitas Multimedia Nusantara, 2022)
Web Ultima Infosys is one of the websites owned by Multimedia Nusantara University (UMN) which contains a collection of journals majoring in information systems. Based on the results of a survey conducted on the use of the Ultima Infosys website for information system students, many students feel that the appearance of the website is lacking or difficult to use. Especially in journal search and journal submission. Therefore, the usability evaluation of the Ultima Infosys web was carried out. The method used in this research is a usability test and system usability scale (SUS). Where the researcher will evaluate using questionnaires and interviews. The results of the questionnaire were measured using SUS. Based on the results of the evaluation score that has been measured by SUS, the result is a score of 50.25. Knowing that the score is below the average, a recommendation for improvement is made in the form of a recommendation mockup. After re-testing and measuring using SUS, the mockup of the recommendation results got a value above the average of 81,265. Thus, it can be concluded that the mockup of the recommendations proved to be easier to understand and use by users.